Harmful sexual practices and gender conceptions in Kwazulu-Natal and their effects on the HIV/AIDS pandemic - Rauch, Rena (Rena Petronella) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2003.